Analisis ANALISIS HUKUM EKONOMI SYARIAH TENTANG PENGATURAN SISTEM PEMBAYARAN DIGITAL SYARIAH DI INDONESIA - Yusran Al Miski; Alif Firmansyah; Wayne Gladys Octatiana Bella; Deva Inggria; Diego MPS (Sekolah Tinggi Ilmu Syariah Darul Falah Bondowoso, 2025)
The development of financial technology (fintech) has significantly transformed digital payment systems in Indonesia, including in the context of Islamic economics. This study aims to analyze the regulation of sharia-compliant digital payment systems in Indonesia from the perspective of Islamic economic law. A normative juridical method is used, analyzing laws, fatwas, and literature related to sharia-based digital financial transactions. The study recommends strengthening regulatory frameworks, enhancing public education, and fostering collaboration among authorities, industry players, and academics to ensure the inclusive and sharia-compliant development of digital payment systems. Keywords: Digital Payment System, Sharia, Fintech, Regulation, Indonesia